Influence of Brand Equity on Electronic-Word of Mouth Mediated by Brand Love on Shopee E-commerce - Harisandi, Prasetyo; Hurriyati, Ratih; Dirgantari, Puspo Dewi (International Journal of Multidisciplinary Approach Research and Science, 2024)
This study aims to explore the impact of Brand Equation on E-Word of Mouth E-commerce in Indonesia. In addition, brand love was studied as a mediator of Brand Equity and E-Word of Mouth activities. Data was collected from a total of 160 Shopee E-commerce users in Indonesia through a structured questionnaire and hypotheses were examined using the PLS model. The results validate that Brand Equity activities have a significant influence on Brand Love directly. E-Word of Mouth is directly influenced by Brand Love. In addition, Brand Love completely mediates the relationship between Brand Equity activities and E-word of mouth has an indirect influence. First, the sample size was limited to 160 respondents, most of whom came from Jabodetabek, Indonesia. It is recommended that future research use larger sample sizes and include individuals from various industry scenarios. Second, this research only focuses on brand equity, e-word of mouth through the mediation of brand love in the e-commerce retail industry. These research suggestions will help the e-commerce retail sector build consumer trust, which will grow Shopee's user base and enable it to better understand its customers' needs through several improvements that will increase customer engagement. Apart from that, it also increases the level of customer involvement itself by creating games, or vision and mission which can later be exchanged for various kinds of promotions tailored to user needs.